Biochemical markers in saliva of patients with diabetes mellitus - Anđelski-Radičević Biljana; Dožić Radica; Todorović Tatjana; Dožić Ivan (Serbian Medical Society - Dental Section, Belgrade, 2012)
Diabetes mellitus is metabolic syndrome characterized by disorder in metabolism of carbon hydrates, lipids and proteins. The diagnosis of diabetes is established by measuring the blood glucose level using standardized methods. Frequent monitoring of blood glucose level could be inconvenient for patients because of possible pain during blood sample taking. In the last few years biological materials with non invasive sampling, like saliva, have been analyzed. Research has confirmed that some organic and inorganic components of saliva are modified in diabetic patients (glucose, lipid and protein components, oxidative stress markers, electrolytes). Beside other markers, the analysis of glucose in saliva is an attempt to find a non-invasive and painless way for frequent monitoring of glucose concentration in diabetic patients. Collecting saliva is simple and economical, it neither requires expensive equipment nor specially trained staff. Saliva can be taken many times and in unlimited quantity. In regards to the data about the possibilities for using saliva as biological sample in monitoring diabetes mellitus, which could be alternative to blood serum or plasma, the conclusion is that saliva becomes more important in this context.